Official Policies and Economic Prospects - Crum, W. L. (The Review of Economics and Statistics, 1934)
T HE present economic situation is controlled by three groups of forces: natural revival forces, official recovery stimulants, and the reform program. It is not my purpose to dwell upon classification niceties, but brief attention to such points will serve as a helpful beginning. We might instructively classify the items of the official economic program under three heads -relief, recovery, and reform. In such a classification the relief items, or those concerned primarily with relief, would bulk very large. A two-category classification, which merges relief with the others, brings out a most important clash of opinion as to public policy: the clash concerning the wisdom of jeopardizing recovery in order to achieve reform. Earlier, indeed, a clash of opinion appeared on another point: should we attempt a stimulated recovery, or let nature take its course? It is doubtful if, by the spring of I933, any considerable body of opinion favored entire reliance upon so-called natural forces for a cure of the depression. Even the outgoing Federal Administration had taken energetic actions, in limited areas, to facilitate or promote recovery. But a very substantial body of opinion not very popular among the mass, and particularly the suffering mass, of our people clearly favored a main reliance upon these natural forces. According to this opinion a more or less natural recovery had already begun in the summer of I932; the I933 bank crisis was a final, and perhaps avoidable, destructive episode in the readjustments incident to the depression; the reopening of the banks and the other confidence-restoring incidents at that time provided the essential impulse toward a vigorous upward movement; and government actions might well be confined largely to granting specific relief in certain areas where hardship was so acute as to impede general recovery. Under existing political auspices this issue as to whether natural forces should be relied upon is largely academic: the present Administration from the start insisted on action. Once that decision had been made and it had undoubtedly been reached long before March I933 it was certain that official policy would aim at stimulated, rather than natural, recovery. Even after this basic decision was made and became known, some critics still urged that all stimulants should be withdrawn as promptly as possible, and that natural forces should be allowed to resume their functioning. This view, in its extreme form, has little chance of being heard under existing political conditions; but in its moderate form it is likely to have and is already having important influence upon public policy.